2018
DOI: 10.1126/science.aao0702
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal ripples down-regulate synapses

Abstract: The specific effects of sleep on synaptic plasticity remain unclear. We report that mouse hippocampal sharp-wave ripple oscillations serve as intrinsic events that trigger long-lasting synaptic depression. Silencing of sharp-wave ripples during slow-wave states prevented the spontaneous down-regulation of net synaptic weights and impaired the learning of new memories. The synaptic down-regulation was dependent on the -methyl-d-aspartate receptor and selective for a specific input pathway. Thus, our findings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
179
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(208 citation statements)
references
References 43 publications
13
179
0
Order By: Relevance
“…It is currently controversial whether hippocampal synapses are potentiated or exclusively depressed during SWRs (Bukalo, Campanac, Hoffman, & Fields, ; Buzsaki, ; Buzsaki, Haas, & Anderson, ; Colgin, Kubota, Jia, Rex, & Lynch, ; King, Henze, Leinekugel, & Buzsaki, ; Leonard, Mcnaughton, & Barnes, ; Norimoto et al, ; Sadowski, Jones, & Mellor, ; Tononi & Cirelli, ). Nevertheless, both synaptic potentiation and depression have been proposed as mechanisms for memory consolidation (Bukalo et al, ; Norimoto et al, ; Sadowski et al, ; Tononi & Cirelli, ). Those hippocampal synapses supporting frequently replayed rewarding sequences may be further strengthened and/or other synapses are weakened during SWRs, so that relative strengths of frequently replayed sequences are enhanced.…”
Section: Implementation Of the Simulation‐selection Modelmentioning
confidence: 99%
“…It is currently controversial whether hippocampal synapses are potentiated or exclusively depressed during SWRs (Bukalo, Campanac, Hoffman, & Fields, ; Buzsaki, ; Buzsaki, Haas, & Anderson, ; Colgin, Kubota, Jia, Rex, & Lynch, ; King, Henze, Leinekugel, & Buzsaki, ; Leonard, Mcnaughton, & Barnes, ; Norimoto et al, ; Sadowski, Jones, & Mellor, ; Tononi & Cirelli, ). Nevertheless, both synaptic potentiation and depression have been proposed as mechanisms for memory consolidation (Bukalo et al, ; Norimoto et al, ; Sadowski et al, ; Tononi & Cirelli, ). Those hippocampal synapses supporting frequently replayed rewarding sequences may be further strengthened and/or other synapses are weakened during SWRs, so that relative strengths of frequently replayed sequences are enhanced.…”
Section: Implementation Of the Simulation‐selection Modelmentioning
confidence: 99%
“…Periods of rest between treadmill running sessions were likely essential to regenerate the network potency for plasticity, as the place field emergence rate progressively decreased across trials within each session ( Figure 4D). Synaptic normalization, especially, might require sleep and sharpwave-ripple oscillations to develop (Norimoto et al, 2018;Vyazovskiy et al, 2008), considering the relatively slow rate of synaptic downscaling observed in vitro (Royer an Paré, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a second possible way to selectively increase the relative strength of synaptic connections underlying newly encoded memories is to weaken synaptic connections between neurons that do not store novel information. Several studies have suggested that SWRs can weaken synaptic strength (Colgin et al, 2004; Bukalo et al, 2013; Norimoto et al, 2018). In particular, a recent study reported that silencing SWR-related neuronal activity during NREM sleep prevents spontaneous weakening of synapses and impairs subsequent learning of new memories (Norimoto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that SWRs can weaken synaptic strength (Colgin et al, 2004; Bukalo et al, 2013; Norimoto et al, 2018). In particular, a recent study reported that silencing SWR-related neuronal activity during NREM sleep prevents spontaneous weakening of synapses and impairs subsequent learning of new memories (Norimoto et al, 2018). This study further showed that place cells active in a novel environment maintained their firing rates during SWRs across NREM sleep while other hippocampal cells’ firing rates gradually declined during SWRs across the course of NREM sleep.…”
Section: Discussionmentioning
confidence: 99%